الحكايةالخرافيةبين الدرس البنيوي السيميائي والدرس الأنثروبولوجي عندالدارسين الجزائريّين - بورايو, عبد الحميد (Changement Social, 2018)
A number of academicstudies  have dealtwith the  Algeriansfalk tales  from a variety of perspectives, including the study of Kamal Abdou and ZahiaTraha, and mydifferentworks and analysis  on a rich corpus collectedfromdifferent parts of Algeriaduring the last quarter of the last century. In dealingwithfairy tales told by women in the Jijel region, Kemal Abdo, by linking the discourse and the externalcircumstancethatcontrolsit, especially temporal and spatial conditions, raises the question of the conditions of women in a masculine society aimedatextendingtheir influence and directingthemaccording to their vision of social relations. For itspar,t in herfieldstudy of the remarkable tribal tale, TrahaZahiacontrasted the reality of women and men in tribal lands, and the fictional image presented to them by the tales. The concepts of surface structure and deep structure have been adopted as a basis for this interface between reality and imagination; between the experience of daily life and the symbolicrepresentation of thisexperience. The surface structure represented the social, geographical and economic reality, while the deep structure embodied the imaginative and artisticrepresentationsembodied in the events of the remarkable story.